PENGEMBANGAN MEDIA PEMBELAJARAN ARTICULATE STORYLINE 3 BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF IPA SISWA KELAS V SDI ANWARUL JAM’IYYAH - latipah, lala; Barokah, Awalina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Based on observations and interviews with grade V teachers of SDI Anwarul Jam’iyyah, students have achieved the KKM score but are not yet optimal. The absence of appropriate learning media makes students feel bored and pay less attention to the subject matter. This study aims to develop, test the validity and effectiveness of articulate storyline 3 learning media based on problem based learning of natural events material. The location of the research was carried out at SDI Anwarul Jam’iyyah, Lenggahsari Village, Cabangbungin District, Bekasi Regency, in the 2024/2025 Academic Year. This research is a development research (Research and Development) developed by Zef Risal, Rachman Hakim and Aminol Rosid Abdullah using the ADDIE model. Expert assessment shows that the articulate storyline 3 learning media based on problem based learning is feasible as a learning media by making revisions based on expert advice. The percentage given by media experts is 95.8%, by material experts is 95% and language experts 85.7%. The average cognitive learning outcomes in the student pretest are 50% and the average posttest is 85%. These results are categorized as very good media to use to improve cognitive science learning outcomes.